Neglected leafy green vegetables crops in Africa: Vol. 2: Bibliography of the genetic resources of traditional African vegetables - Mnzava, N.M.; Dearing, J.A.; Guarino, Luigi; hweya, J.A.; Koeijer, H. de (1999)
This bibliography focuses on bibliographic references that give results of research undertaken with the intention of understanding the genetic base of traditional vegetables. Researchers collaborating with the editors decided on the major species and subjects to be included in this publication. References were obtained not only from the international agricultural databases CAB Abstracts, AGRIS and AGRICOLA but also from grey litreature collected by the compilers. As many traditional vegetables from Africa can be found in other continents, relevant studies on the same species are also included in this bibliography.This bibliography does not claim to be definitive or even exhaustive. We are aware of the fact that results of research undertaken by African researchers and students is still to be published or can not be found in the international bibliographic databases. Therefore we welcome information on papers, reports and thesis written on Africa's traditional vegetables that are not included in this bibliography. This information will stimulate and help us to produce a second volume of this bibliography.